ABOUT THE ROLE OF ROAD MAPS IN THE ELECTRONIC TRAINING TECHNOLOGY TO COMPUTER SCIENCE STUDENTS OF CLASSICAL UNIVERSITY - Nadezhda M. Andreeva; Nickolai I. Pak (Открытое образование (Москва))
The results of the analysis causes dissatisfaction with the TRAINING process of students to computer science are presented. The didactic principles of teaching from the viewpoint of perspective of ICT were refi ned. The structure of the information subject environment of teaching computer science for the individualization of teaching students with the use of road maps is described. The technique of the road maps at training of students is presented and the results of pedagogical experiment are shown.